Analisis Pola Penyebaran Investasi Dan Faktor Yang Mempengaruhinya Di Provinsi Sumatera Barat - Rizki Adi Putra; Alpon Satrianto (Jurnal Ekonomi, 2024)
Investment is basically the initial stage of economic development. The influx of investment has a positive impact on regional development, so the government's role is needed to attract new investors. This research aims to analyze the distribution of investment patterns and the extent of the influence of per capita income, infrastructure, labor and crime on investment in West Sumatra Province. This research uses panel data obtained from various government institutions during the time period 2017 - 2021. The methods used in this research are theil entropy index and panel data regression. The research results show that the pattern of investment distribution initially tended to be spread out and changed to tend to be concentrated in the category of moderate inequality, crime has a negative and significant effect on investment, while per capita income, infrastructure and labor do not have a significant effect on investment.